Dihydromyricetin ameliorates vascular calcification in chronic kidney disease by targeting AKT signaling. Issue 21 (12th November 2021) - Feng, Liyun; Que, Dongdong; Li, Zehua; Zhong, Xinglong; Yan, Jing; Wei, Jintao; Zhang, Xiuli; Yang, Pingzhen; Ou, Caiwen; Chen, Minsheng
Abstract: Vascular calcification is highly prevalent in chronic kidney disease (CKD), and is characterized by transdifferentiation from contractile vascular smooth muscle cells (VSMCs) into an osteogenic phenotype. However, no effective and therapeutic option to prevent vascular calcification is yet available. Dihydromyricetin (DMY), a bioactive flavonoid isolated from Ampelopsis grossedentata, has been found to inhibit VSMCs proliferation and the injury-induced neointimal formation. However, whether DMY has an effect on osteogenic differentiation of VSMCs and vascular calcification is still unclear. In the present study, we sought to investigate the effect of DMY on vascular calcification in CKD and the underlying mechanism. DMY treatment significantly attenuated calcium/phosphate-induced calcification of rat and human VSMCs in a dose-dependent manner, as shown by Alizarin Red S staining and calcium content assay, associated with down-regulation of osteogenic markers including type I collagen (COL I), Runt-related transcription factor 2 (RUNX2), bone morphogenetic protein 2 (BMP2) and osteocalcin (OCN). These results were further confirmed in aortic rings ex vivo . Moreover, DMY ameliorated vascular calcification in rats with CKD. Additionally, we found that AKT signaling was activated during vascular calcification, whereas significantly inhibited by DMY administration. DMY treatment significantly reversed AKT activator-induced vascular calcification. Furthermore, inhibition of AKT signaling efficiently attenuated calcification, which was similar to that after treatment with DMY alone, and DMY had a better inhibitory effect on calcification as compared with AKT inhibitor. The present study demonstrated that DMY has a potent inhibitory role in vascular calcification partially by inhibiting AKT activation, suggesting that DMY may act as a promising therapeutic candidate for patients suffering from vascular calcification.